Near-infrared brain imaging study of depressive disorder with liver qi stagnation syndrome before and after treatment - Chen, Gui-Fang; Mao, Meng-Chai; Yu, Chen-Chao; Feng, Kun; Wang, Xin-Yu; Xu, Dong-Sheng; Liu, Po-Zi (Frontiers in Psychiatry, 2025)
ObjectiveThis study is a cohort study of depressive disorder patients with liver qi stagnation syndrome specified under the theory of Integrated Chinese and Western Medicine (ICWM). They were measured hemodynamic activity, using fNIRS assessment with verbal fluency task (VFT) pre-treatment and post-treatment, to examine the neurophysiological characteristics, and to explore the impact of drug treatment on it.MethodsThis study recruited patients who were diagnosed with depressive episodes according to the DSM-V diagnostic and Traditional Chinese Medicine (TCM) diagnostic criteria in the outpatient department of Yuquan Hospital Tsinghua University. 35 patients who met the criteria were recruited. All patients were treated with selective serotonin reuptake inhibitors (SSRIs) drugs. The clinical evaluation, VFT and fNIRS assessment were performed pre-treatment and post-treatment two times. After 3 months of treatment, the clinical evaluation, VFT and fNIRS assessment were performed again as a follow-up assessment for the third time.ResultsThere were statistically significant differences in HAMD scores between pre-treatment and follow-up assessment (p =0.037), with the total scores of HAMD significantly decreased in follow-up assessment. The lDLPFC and mPFC activation in fNIRS during VFT was significantly increased after treatment, as compared to pretreatment assessment, in CH13(p = 0.003) and CH30 (p = 0.035), and the improvement at lDLPFC remained in the follow-up assessment in CH13 (p = 0.007).ConclusionThis indicates that the activation of the lDLPFC improved after the treatment, and this improvement can remain stable. Hemodynamic activation can reflect the changes of brain function after the one-month treatment, even before the changes of clinical symptoms in depression liver-qi stagnation syndrome. Physiological indicators like fNIRS result may better reflect the improvement of depression liver-qi stagnation syndrome than ethological indicators like HAMD.